Extending the theory of planned behavior: A study of lifestyles, contextual factors, mobile viewing habits, TV content interest, and intention to adopt mobile TV. Issue 8 (December 2017) - Leung, Louis; Chen, Cheng
Highlights: This study demonstrated the robustness of TPB in explaining adoption intention of mobile TV. Channel deficiency, mobile viewing habit, and content interests significantly influence adoption intention of mobile TV. Effects of mobile viewing habit on consumers' adoption intention of mobile TV was moderated by perceived behavioral control. Lifestyles had strong effect on content interests in mobile TV. Males were more likely to use mobile TV. Abstract: This study applied the theory of planned behavior (TPB) to explain the intentions of Hong Kong consumers to adopt mobile TV and their interests in its content. Using a probability sample of 644 respondents, this study not only demonstrated the robustness of TPB in explaining consumer behavior but also showed that channel deficiency, mobile viewing habits (which were moderated by perceived behavioral control), and content interest could significantly influence consumers' intentions to adopt mobile TV services. Although lifestyle types were not found a significant predictor of behavioral intention, it had strong effect on content interests in mobile TV. Limitations and practical implications are provided.